2013
DOI: 10.1172/jci64398
|View full text |Cite
|
Sign up to set email alerts
|

GSK-3α is a central regulator of age-related pathologies in mice

Abstract: Aging is regulated by conserved signaling pathways. The glycogen synthase kinase-3 (GSK-3) family of serine/ threonine kinases regulates several of these pathways, but the role of GSK-3 in aging is unknown. Herein, we demonstrate premature death and acceleration of age-related pathologies in the Gsk3a global KO mouse. KO mice developed cardiac hypertrophy and contractile dysfunction as well as sarcomere disruption and striking sarcopenia in cardiac and skeletal muscle, a classical finding in aging. We also obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
126
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(134 citation statements)
references
References 52 publications
(48 reference statements)
2
126
2
4
Order By: Relevance
“…Whereas GSK3␤ knockout is embryonically lethal (35), GSK3␣ knock-out mice are viable, although they manifest accelerated aging and cardiac hypertrophy (36). An interesting finding to emerge from our studies is that GSK3␤ is preferably inactivated in diabetic kidney injury; SNP stimulated GSK3␤ rather than the GSK3␣ isoform, which was sufficient to ameliorate diabetic kidney injury.…”
Section: Discussionmentioning
confidence: 75%
“…Whereas GSK3␤ knockout is embryonically lethal (35), GSK3␣ knock-out mice are viable, although they manifest accelerated aging and cardiac hypertrophy (36). An interesting finding to emerge from our studies is that GSK3␤ is preferably inactivated in diabetic kidney injury; SNP stimulated GSK3␤ rather than the GSK3␣ isoform, which was sufficient to ameliorate diabetic kidney injury.…”
Section: Discussionmentioning
confidence: 75%
“…Notably, TA structures were not observed either in the gastrocnemius of young WT male mice or in the gastrocnemius of prematurely aged Cisd2 mKO male mice at 3 months of age. These findings may be attributable to the age of the mice as the formation of TAs appears to be a time‐dependent process requiring a long incubation time to allow for the gradual formation of TAs (Lahoute et al., 2008; Nishikawa et al., 2000; Zhou et al., 2013). Furthermore, a previous study has shown that Casq and Serca both participate in TA development.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in mice, GSK3␤ global knockout (GSK3␤KO) causes lethality, whereas mice lacking GSK3␣ are viable and fertile, suggesting that GSK3 isoforms are not functionally redundant during embryonic development (13,18,26). Postnatally, GSK3␣ is critical for the heart's ability to respond to hemodynamic stress and aging in mice (51,52). GSK3␣ and GSK3␤ isoforms also exhibit distinct functions in cardiac cell proliferation, glucose tolerance, glycogen synthesis, and regulation of transcription factors (18,25,26,33).…”
mentioning
confidence: 99%